Organizational and Pedagogical Conditions for the Educational Process Implementation within the Inclusive Education in the Republic of Kazakhstan - Shalbayeva, D.Kh; Zhetpisbayeva, B.A.; Akbayeva, G.N.; Assanova, D.N. (European Journal of Contemporary Education, 2021)
The present article aims to identify the major problems English teachers face in the process of working with special educational needs learners in the context of inclusive education in general education schools of the Republic of Kazakhstan. Despite the studies on special methods and pedagogy of inclusive education carried out by the educators, there are still no inclusive education achievement indicators enshrined in law. The study uses the following general scientific methods: analysis of the current and prior normative legal acts regulating teachers’ activities in the field of inclusive education, analysis of scientific and methodological literature on special, general, and inclusive education, synthesis of definitions of inclusive education concepts as well as a survey of English teachers. The conducted survey demonstrates a range of material, technical, pedagogical, and specific subject-related problems the teachers face in the context of inclusive education. Such problems are determined by the specifics and distinctive characteristics of teaching the English language in inclusive education conditions, as well as the preceding absence of courses on the methods of teaching the English language in inclusive education in the programs of higher educational establishments. One of the main problems identified by the study was insufficient level of teacher training courses to prepare for teaching within the inclusive education, as well as the lack of appropriate methods on teaching English in an inclusive classroom. Thereunder, current article describes some practical ways of addressing problems defined.
Keywords: individual differences; individual learning; inclusive education; language teaching; learning environment; special methods; special educational needs; talented and gifted learners